The frogs and toads all sang - Lobel, Arnold; Lobel, Adrianne (New York : HarperCollins Children's Books, 2009)
Presents a linked collection of ten short stories in rhyme featuring frogs, toads, and polliwogs.
The frogs and toads all sang -- Miss Frog went in the kitchen -- I love to eat -- Polliwog school -- Bright green frog -- Made for toads -- There was a frog -- Night -- A toad was feeling-- -- One summer night.
Keywords: Frogs -- Juvenile fiction; Toads -- Juvenile fiction; Tadpoles -- Juvenile fiction; Stories in rhyme